G557(P) An audit of handover of information before and after a brief intervention. (27th April 2016) - Arrowsmith, L; Winter, G; Turner, S
Abstract : Context: To complete an audit of the content of handover before and after an intervention. Problem: Highly variable morning handover in paediatric surgery, often poor quality. Frustrating for both paediatric surgical team and junior doctor on night duty Assessment of problem and analysis of its causes: Night doctor handing over to day team was from paediatric medicine or surgical department. Variablilty in handover became evident very quickly. Cause was thought to be lack of clarity regarding handover content Intervention: A simple tool to aid hand over was designed. Key items required at hand over were identified by junior doctor and consultants in paediatric surgery Study design: An audit of details shared at early morning paediatric surgical handover was completed between April – June 2015. Weekends were not counted as handover takes a different format. Key items required at hand over were identified as priority by the author, and consultants in paediatric surgery. The author attended hand over and decided whether each key item was mentioned. Points audited were recorded in a simple 'yes'/'no' format to observe what information is particularly poorly communicated. Strategy for change: A handover tool was designed and introduced; the tool was a single A4 sheet of paper. Measurement of improvement: The initial audit was repeated using the paper tool to monitor for improvement, re-audit was undertaken from end of June to August 2015. Effects of changes: Table below details% of time information was reported at moning handover. A total of 20 handovers audited before handover tool was introduced, and 21 handovers audited using handover tool. Lessons learnt: A brief intervention with a check list has created a safe reproducible handover. Areas in need of improvement are discussion regarding availability of medical staffing. Message for others: A simple intervention can be applied in multiple settings to improve communication.